Analysis of the Frame Strength on the Paint Mixer Machine Using ANSYS Workbench Software - Paryanto; Anang Dwi Jayanto (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2025)
The era of industrialization requires humans to continuously strive to develop technology, one of which is the semi-automatic paint mixer machine. The purpose of this research is to determine the strength of the mixer machine frame and the motor mount frame of the paint mixer machine, through the analysis of von Mises stress, deformation, and safety factor. This research is a quantitative study using a descriptive method. The research design involves finite element method simulations using Ansys Workbench 2023 R1 software. Data collection techniques used are observation and documentation. Data analysis is performed using descriptive statistical techniques. The maximum von Mises stress analysis in areas 1, 2, and 3 resulted in values of 0.2975 MPa, 2.2619 MPa, and 3.4034 MPa, respectively. These results are still well below the yield strength of ASTM A36 material. This occurs around the area where the load is applied near the joint. The maximum deformation analysis in areas 1, 2, and 3 yielded results of 0.00038 mm, 0.00415 mm, and 0.0274 mm, respectively. This occurs around the area near the front edge where the load is applied away from the joint. The safety factor analysis in areas 1, 2, and 3 resulted in a value of 15. This exceeds the required safety factor, indicating that the frame is safe to withstand the applied loads.